Psychiatric Morbidities in Patients With Primary Headache - Gautam, Sanjeev Chandra; Bhattarai, Yash; Singh, Pradip Man (Journal of Gandaki Medical College-Nepal, 2020)
Background: Headache is a pain that occurs above the eyes or the ears, behind the head in the occiput or the cervical region of neck. A primary headache is a type of headache that is caused by overactivity of the problems with pain-sensitive structures in your head and is not a symptom of an underlying disease condition in a patient. This study highlights on the association of Primary Headaches with psychiatric morbidities and stressful life events that may cause or increase the severity of Primary Headache and its psychiatric co-morbidities.Descriptive, Cross-Sectional, Hospital Based study was done in 75 patients who met the diagnostic criteria for Primary Headache. Results: Patients presenting with primary headache were of the age group 26-30(26.7%) followed by 21-25 and 31-35. 57.3% were female patients and 69.3% were married.  29.3% of the patients were housewives, 25.3% were into service and 21.4% were students. Majority of the patients had literacy upto Bachelors degree (32%). Anxiety and depression were the major diagnosis with 22.3 and 17.4 % respectively, they were also the major co-morbid conditions. Illness in the family and self or family member unemployment were the major stressful life events. There was a significant relation of Psychiatric Morbidity with Primary Headache. Conclusion: Anxiety disorder was the major morbid and comorbid psychiatric condition found in patient with Primary Headache followed by depression. This was seen majorly in female and of the age group 26-30 years of age and the patients who were married. Thus is it is necessary to screen Primary Headaches and reduce the stressful life events in these patients and limit the consequences and outcome of Primary Headache to prosper the health and living standard of the patients and the population as a whole.